A LINGUISTIC PICTURE OF THE WORLD IN PHILOSOPHICAL-EDUCATIONAL ASPECT - Ашиток, Н. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the specifics of forming of modern linguistic picture of the world in consciousness of young people in philosophical and educational context are examined, problems which arise up during this process are probed.